Adverse Selection in Low-Income Health Insurance Markets: Evidence from an RCT in Pakistan - Fischer, Torben; Frölich, Markus; Landmann, Andreas (American Economic Journal: Applied Economics, 2023)
We present robust evidence on adverse selection in hospitalization insurance for low-income individuals that received first-time access to insurance. A large randomized control trial from Pakistan allows us to separate adverse selection from moral hazard, estimate how selection changes at different points of the demand curve, and test simple measures to limit adverse selection. The results reveal substantial selection in individual policies, leading to welfare losses and the threat of a market breakdown. Bundling insurance policies at the household level or higher almost eliminates adverse selection, thus mitigating its welfare consequences and facilitating sustainable insurance supply. <br